Bats of Georgia - an occurrence dataset from 1835 through 2022 - Ioseb Natradze; Alexander Buknikashvili; Giorgi Sheklashvili; Levan Mumladze (Biodiversity Data Journal, 2023)
In Georgia, currently, 30 species of bats are recorded from four families and eleven genera. Although the oldest record of bats is from 1835 and continues until today, there are no comprehensive data available for bat diversity and distribution in Georgia. Thus, we aimed to fill that gap and make complete, expertly curated literature and our own published data openly available (through GBIF) for researchers and conservationists.In this publication, out of 1987 records, 1243 (62.4%) are new and unpublished data. Generally, out of all records, 34% are literature and museum data and 66% are data collected by us. Additionally, for the first time in the history of the study of bats in Georgia, we initiated surveys in forested areas of the country.